Adding salt to foods and hazard of premature mortality. (30th June 2022) - Ma, Hao; Xue, Qiaochu; Wang, Xuan; Li, Xiang; Franco, Oscar H; Li, Yanping; Heianza, Yoriko; Manson, JoAnn E; Qi, Lu
Abstract: Aims: We analyzed whether the frequency of adding salt to foods was associated with the hazard of premature mortality and life expectancy. Methods and results: A total of 501 379 participants from UK biobank who completed the questionnaire on the frequency of adding salt to foods at baseline. The information on the frequency of adding salt to foods (do not include salt used in cooking) was collected through a touch-screen questionnaire at baseline. We found graded relationships between higher frequency of adding salt to foods and higher concentrations of spot urinary sodium or estimated 24-h sodium excretion. During a median of 9.0 years of follow-up, 18 474 premature deaths were documented. The multivariable hazard ratios [95% confidence interval (CI)] of all-cause premature mortality across the increasing frequency of adding salt to foods were 1.00 (reference), 1.02 (0.99, 1.06), 1.07 (1.02, 1.11), and 1.28 (1.20, 1.35) ( P -trend < 0.001). We found that intakes of fruits and vegetables significantly modified the associations between the frequency of adding salt to foods and all-cause premature mortality, which were more pronounced in participants with low intakes than those with high intakes of these foods ( P -interaction = 0.02). In addition, compared with the never/rarely group, always adding salt to foods was related to 1.50 (95% CI, 0.72–2.30) and 2.28 (95% CI, 1.66–2.90) years lower life expectancy at the age of 50 years in women and men, respectively. Conclusions: Our findings indicate that higher frequency of adding salt to foods is associated with a higher hazard of all-cause premature mortality and lower life expectancy. Structured Graphical Abstract: Structured Graphical Abstract Adding salt to foods and hazard of premature mortality.